Determination of the association of minimum inhibitory concentrations of antituberculosis drugs and resistance mutations of clinical isolates of mycobacterium tuberculosis from Limpopo, Province, South Africa - Malope, Pleasure (My University, 2025)
Background: Tuberculosis (TB) maintains its position as the leading global infectious disease, and South Africa is among the countries most affected by drug-resistant strains. The situation of tuberculosis is exacerbated by the emergence of multidrug-resistant tuberculosis (MDR-TB) and extensively drug-resistant tuberculosis (XDR-TB), which presents significant challenges to TB control efforts, especially in regions such as Limpopo Province, where high transmission rates and limited resources worsen the problem. Genetic mutations are the primary drivers of drug resistance, altering the effectiveness of both first-line and second-line antituberculosis drugs. Despite the revolution in TB detection and treatment brought about by molecular diagnostics, it remains necessary to deepen our understanding of how these genetic mutations impact the level of drug resistance. The minimum inhibitory concentration (MIC) of anti-TB drugs, which indicates the lowest concentration needed to inhibit bacterial growth, plays a crucial role in clinical decision making. However, current diagnostic tools often do not account for the correlation between MIC levels and specific resistance mutations, especially for newer drugs like Bedaquiline. This study aimed to address the gap by examining the relationship between MICs and resistance mutations in Mycobacterium tuberculosis clinical isolates from Limpopo province. By utilizing advanced molecular techniques such as whole genome sequencing (WGS) and phenotypic drug susceptibility testing. Methods: This cross-sectional, quantitative study analyzed 281 clinical isolates from the tuberculosis repository of the Polokwane National Health Laboratory Service (NHLS). The MICs for levofloxacin (LVX), moxifloxacin(MXF), and bedaquiline (BDQ) were determined using the BD BACTEC MGIT 960 system. Whole genome sequencing (WGS) was performed on phenotypically resistant clinical isolates to identify mutations associated with drug resistance. Statistical analyses, including T-tests and logistic regression, were performed to correlate MICs with specific resistance mutations.Results: A total of 147 drug-resistant tuberculosis clinical isolates met the study inclusion criteria and were tested for MIC. Seventy-seven (52.4%) isolates were from men in the age group of 26-45 years with a mean age of 39 (IQR 18 to 46) years. A total of 139 (94.6%) were susceptible to LVX while 144 (98.0%) and 128 (87.1%) were susceptible to MXF and BDQ, respectively. Of the eight fluoroquinolone (FLQ)-Not resistant clinical isolates, most were associated with mutations in the gyrA gene. The most common mutations were substitutions in Condon 94 of 6 (75.5%), leading to low-level resistance. In bedaquiline-resistant clinical isolates, mutations were identified in the Rv0678, Rv1979c, and atpE genes, with most mutations linked to increased levels of resistance. Conclusions In conclusion, this study identified key mutations in Mycobacterium tuberculosis clinical isolates from Limpopo province that are associated with resistance to LVX, MXF, and BDQ. These findings highlight the need for continuous monitoring of resistance mutations and MIC levels to inform clinical decision-making and optimize treatment regimens for DR-TB (drug resistant tuberculosis). Understanding the genetic drivers of drug resistance is crucial for developing effective diagnostic tools and therapeutic strategies.
Thesis (M.Sc. (Medical Sciences)) -- University of Limpopo, 2025
Keywords: Tuberculosis; Drug-resistant tuberculosis; Levofloxacin; Moxifloxacin; Bedaquiline; Minimum inhibitory concentration; Mutation; Critical concentration; Whole genome sequencing.; Tuberculosis; Moxifloxacin; Multidrug-resistant tuberculosis